Chronic Recurrent Mastitis: Bangladesh Perspective-10 Years Study in a Tertiary Care Hospital - Shabnam, Nilufar; Choudhury, Md Iqbal Mahmud; Ahsan, Tazin; Akter, Pervin; Ananna, Sabiha Sanjida; Ahsan, SM Abu (Bioresearch Communications, 2022)
Introduction: Granulomatous mastitis is a very significant chronic breast infection poses a lot of challenge for diagnosis and management. Treatment options are ranging from various medical management to different surgical procedure. However, none of the treatment strategy is considered as standard so far. In this study, we showed some investigations and management options for chronic breast infections. Materials and methods: It is a randomized clinical trial done in BIRDEM (Bangladesh Institute of Research and Rehabilitation of Diabetic Endocrine and Metabolic Disorders) Hospital and Ibrahim Medical College from July 2013 to June 2020. We enrolled patients on basis of histopathological report of chronic breast infected patients. Gene X-pert for tuberculosis, MT (Montoux Test) and bacterial culture was done in all enrolled patients. Results: A total of 165 female patients were enrolled in this study. Patient’s age was between 13-68 years with mean age 31.5 years. Maximum 44.85% (76) cases were found in 20-30 yeas age group. Most common clinical presentation non healing discharging ulcer 51.52% (85) followed by mass with abscess 26.02% (43) and mass with sinus 22.42% (37). Diagnosis was confirmed by histopathologically. Idiopathic Granulomatous Mastitis was found in 58.79 %( 97) patients and Tubercular Mastitis in 41.21% (68) patients. Tubercular Mastitis was treated by standard Anti tubercular drugs in 23.72% (37) patients and by additional oral methyl prednisolone in 18.79% (31). 21.82% (36) Idiopathic Granulomatous Mastitis was treated with oral methyl prednisolone and sensitive antibiotic, whereas 36.97% (61) patients needed additional oral methotrexate. Different type of surgical procedures needed in both infections to achieve the goal. Conclusion: We want to share our experience regarding diagnosis and management of different chronic breast infections and final outcome of management Bioresearch Commu. 8(2): 1156-1159, 2022 (July)